Illegal Actions of Cultural Assets in the Republic of Uzbekistan, Prevention of Them and Foreign Experience (Eurasian Research Bulletin, 2023)
The article analyzes some problematic issues that arise in determining responsibility for cases of violations of legislation related to the theft of objects and collections of cultural, historical, archaeological value through forgery, their illegal actions from the customs border, norms concerning criminal liability in the criminal legislation of foreign countries for crimes in the field of customs. In addition, the peculiarities of criminal liability in foreign countries for crimes related to cultural values were considered.